Protective effect of ivy leaf extract on paracetamol-induced oxidative stress and nephrotoxicity in mice - Pedram Moshaei-Nezhad; Seyed Mohammad Hosseini; Mohsen Yahyapour; Maryam Iman; Ali Khamesipour (Shahrekord University of Medical Sciences, 2019)
Introduction: The aim of the study was to evaluate the protective effect of Hedera helix (ivy) leaf extract on paracetamol-induced oxidative stress and renal toxicity in mouse model. Methods: Sixty male Swiss albino mice were randomly divided into six equal groups. Group A: as the control group, received NaCl 0.9%. Group B: received a single (i.p.) injection of paracetamol (600 mg/kg). Pretreatment groups: included T1 (50 mg/kg), T2 (100 mg/kg), T3 (200 mg/kg), and T4 (300 mg/kg) which were treated with ivy leaf extract in different doses. The mice were sacrificed under mild anesthesia and the blood samples were collected to titrate the levels of serum blood urea nitrogen (BUN), creatinine and, uric acid. Kidneys were removed for histopathological examination. Results: Paracetamol administration significantly increased the BUN, creatinine and uric acid levels (P < 0.05). Treatment with Ivy leaf extract resulted in a significant reduction in serum creatinine, uric acid and BUN concentrations in comparison with the paracetamol group. Ivy leaf extract treatment similarly reduced histological alteration induced by paracetamol. Conclusion: This study can be used as prove of reading that ivy leaf extract might be used to prevent renal damage induced by paracetamol.